Pelaksanaan Metode Demonstrasi Pada Ekstrakurikuler Drumband di SMP Negeri 2 Padang - Afifah Hilmi; Irdhan Epria Darma Putra (EDUMUSIKA, 2024)
This research aims to describe the implementation of the demonstration method in extracurricular drumband at SMP Negeri 2 Padang. This research is classified as qualitative research and the method used is descriptive analysis. The research instrument is the researcher himself as the main instrument. Data collection was supported through the stages of literature study, observation, interviews, and audio and video recording during the drumband extracurricular implementation. Drumband extracurricular activities are held once a week, namely Thursday after teaching and learning activities are finished, then this activity is supervised by the arts and culture teacher himself. The results of this research are the implementation of the demonstration method in the drumband extracurricular at SMP Negeri 2 Padang, namely: 1) The implementation of the demonstration method can make it easier for students during the extracurricular activity process. 2) Rhythmic percussion and melodic percussion musical instruments develop better with demonstration methods that help students during the process of carrying out drumband extracurricular activities. 3) Students are more enthusiastic and motivated to take part in drumband extracurricular activities.